Paratekst w serii przekładowej — polskie przekłady dwóch wierszy Milivoja Slavička - Wołek San Sebastian, Katarzyna (Przekłady Literatur Słowiańskich, 2017)
Paratext in a Series of Translations: Polish Translations of Two Poems by Milivoj Slaviček Paratext has a considerable impact on the shaping of the way in which a literary work is open to each translation, as well as the dynamics of this openness. Critical paratexts that refer to an existing translation prove that new attempts arise from the readers’ unfulfilled expectations. Peritexts, where the poetics of a given author is discussed, point out that the aesthetic value of a given work corresponds to the number of readings of that work (including translations). They also provide a justification (albeit not an indirect one) for individual translation solutions, similarly to paratexts, where the translator provides reflections on his or her own translation. On the other hand, elements of critical epitexts (i.e. reviews) oftentimes become an integral part of a new translated text in a series. Keywords: paratext, translation series, Milivoj Slaviček